2012
DOI: 10.1515/jpm.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiretroviral therapy with protease inhibitors in HIV-infected pregnancy

Abstract: Women receiving antiretroviral therapy with PI have a similar rate of premature birth and low birth-weight as women receiving antiretroviral therapy without PI or on no medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…The rate of LBW from our findings (<20%) differ considerably from data reported in Cote d’Ivoire and in India [ 8 , 11 , 12 ], possibly due to higher immunological status among women in our study. In the frame of findings from in Botswana and other African or Latin America settings, immune-compromised pregnant women receiving PMTCT option B+ should thus far be monitored during routine ANC to limit the potentials of foetal growth retardation in RLS [ 14 , 19 , 20 ], in order to achieve similar target performance in the western world [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The rate of LBW from our findings (<20%) differ considerably from data reported in Cote d’Ivoire and in India [ 8 , 11 , 12 ], possibly due to higher immunological status among women in our study. In the frame of findings from in Botswana and other African or Latin America settings, immune-compromised pregnant women receiving PMTCT option B+ should thus far be monitored during routine ANC to limit the potentials of foetal growth retardation in RLS [ 14 , 19 , 20 ], in order to achieve similar target performance in the western world [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, monotherapy (i.e. option A) and cART (option B or B+) used during pregnancy in SSA mostly consist of reverse transcriptase inhibitors, which are drugs with lesser antenatal impairments, compared to protease inhibitor-based regimens commonly used in developed countries [ 11 ]. Thus, understanding the impact of commonly used antiretrovirals on birth outcomes in SSA would serve in designing interventions aiming at: (a) continuing current ART during pregnancy without further interventions, (b) continuing current ART during with specific monitoring measures, or (c) switching from current ART to potential regimens with safer birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 ] For example, two papers reported that preterm birth rates were similar to those found in a HIV negative population. [ 46 , 47 ] One study argued ART by itself may not be sufficient for decreasing the burden of adverse birth outcomes in HIV positive women without nutritional care. [ 33 ] The potential harm to the fetus from maternal ingestion of a drug not only depends on the drug itself, but on the dose, the gestational age at exposure, the duration of exposure, the interaction with other agents, and to an unknown extent, the genetic makeup of the mother and fetus.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies implicated PIs directly, and more specific studies have reported no association between PI-based regimens and SGA 40,54,55. Likewise, the randomized Kesho Bora trial showed no significant increase in low (<2,500 g) or very low (<1,500 g) birth weights in the PI-based HAART arm 6.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%